TINJAUAN POTENSI WISATA DI OBJEK WISATA TARUSAN KAMANG KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Septuri, Ferro Libes; Silfeni, Silfeni; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research to describe about tourism potential at Tarusan Kamang Kecamatan Kamang Magek consist of what to see, (b) what to do, (c) what to buy, (d) what to arrived, (e) what to stay.The kind of research is descriptive qualitative. Technique data collection was carried out by using the method interview, observation and documentation. In this research using purposive sampling with 6 informants snowball sampling with 5 informants. Technique analysis data used in this research was reduction data, presentation of data, and conclusion.The research found that Tarusan Kamang object seen from the aspect: (a) what to see, Tarusan Kamang has a beautiful scenery. (b) what to do, tourist can take Rakit and boat around Tarusan Kamang. (c) what to buy, there is no souvenir shop, but tourist can only find the tradisional food. (d) what to arrived, the transportation which available is land transportation mode. (e) what to stay, there is nor accomodation available at Tarusan Kamang .Keywords: Tourism Potential, Tourism Object